Pemberdayaan Satgas Gotong Royong Berbasis Desa Adat Dalam Pencegahan COVID-19 di Banjar Serongga Pondok, Tabanan - Putu Nita Cahyawati; A. A. Sri Agung Aryastuti; Luh Gde Evayanti (Lembaga Penelitian, Universitas Warmadewa, 2020)
The COVID-19 pandemic is affecting all elements of Indonesian society. Lack of knowledge, lack of readiness, and insufficient allocation of funds make the prevention of this disease a challenge for the entire community. Social distancing, limiting all activities outside the home, using masks, hand sanitizers and disinfectants are all efforts that can be made to prevent the spread of this disease. Banjar Serongga Pondok is one of the traditional Banjar which is quite consistent in implementing these things. The residents of Banjar Serongga Pondok have indeed tried to reduce all activities outside the home, but it is undeniable that there are still residents who have not been able to implement this properly. Therefore, a special task force was formed called the Satgas Gotong Royong Berbasis Desa Adat as the driving force for all COVID-19 virus prevention activities in Banjar. The routine efforts that usually they do are spraying disinfectant liquid every Sunday. However, the limitations of disinfectant fluids and budget constraints in the implementation of these activities made it difficult to carry out the activities. The condition, exacerbated by the scarcity of masks, also made it difficult for the task force to work for residents. Based on these problems, the service is focused on providing information related to COVID-19, providing masks, hand sanitizers, and disinfectants to the COVID-19 Task Force in Banjar Serongga Pondok. The activity was started by giving a speech by Kelian Adat Banjar Serongga Pondok, remarks by the head of the activity organizer, material delivery and discussion, the delivery of assistance, and assistance in the implementation of disinfection. This program is expected to help the task force's work program continuity in preventing the transmission of COVID-19, especially in Banjar Serongga Pondok.